Spirituality and God-attachment as predictors of subjective well-being for seminarians and nuns in India - Mendonca, Dudley (Research in the social scientific study of religion, 2007)
The present study was a cross-sectional study of spirituality and views of God as predictors of subjective well-being (SWB) over and above a comprehensive measure of personality. The total sample of 321 participants consisted of 121 Catholic religious women and 200 Jesuit seminarians in India whose overall mean age was 34 years. Family of origin backgrounds of the participants were severely impoverished economically. Hierarchical multiple regression found that personality explained a significant amount of variance for all three facets of SWB including positive affect, negative affect, and cognitive well-being. Faith maturity and positive God image each contributed significant independent variance in predicting increased positive affect and cognitive well-being. Negative God-image, in contrast, predicted reduced positive affect and cognitive well-being, and increased negative affect. Analysis by gender indicated that spirituality and God image predict differentially to subjective well-being components for men and women. The findings replicate cross-culturally the utility of viewing spiritual transcendence as related to human flourishing.